Refusal to implement a foreign arbitration award in accordance with the 1958 New York Convention : Analytical Study - Shno Hamad Adullah; Zahir Majeed Qader (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
This research deals with the issue of refusing to implement a foreign arbitration award, according to the provisions of the New York Convention of 1958. This agreement divided cases of refusal to implement a foreign arbitral award into two parts, cases of refusal to implement at the request of the opponent, and cases of refusal to implement which the competent court decides on its own. Whereas the New York Convention gives the state required to implement the foreign arbitral award on its territory the right to refuse to implement this judgment if the opponent submits to the competent authority therein evidence of the availability of one of the cases stipulated in Article 5 of the Convention. From this point of view, and in order to understand the various aspects of this subject, we divided this research into two sections: In the first section, we dealt with the refusal to implement the foreign arbitral award for objective reasons, through four sub. As for the second topic, we devoted it to showing cases of refusal to implement a foreign arbitral award for procedural reasons, through three demands. The researcher reached a set of conclusions and recommendations, one of the most important conclusions is that under the New York Convention, the contracting state may refuse to recognize and implement a foreign arbitration award on its own because of the inability of the subject of the dispute to arbitration. However, the agreement did not clearly and explicitly state the term “the subject of the dispute,” and did not specify the types of issues that can be settled through arbitration، The determination of this issue is left to the law of the country in which implementation is required.